2016
DOI: 10.1002/mbo3.402
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the phosphodiesterase BifA facilitating swimming motility is partly controlled by FliA inPseudomonas putidaKT2440

Abstract: Flagella‐mediated motility is an important capability of many bacteria to survive in nutrient‐depleted and harsh environments. Decreasing the intracellular cyclic di‐GMP (c‐di‐GMP) level by overexpression of phosphodiesterase BifA promotes flagellar‐mediated motility and induces planktonic lifestyle in Pseudomonas. The mechanism that regulates expression of bifA gene was poorly studied. Here we showed that expression of BifA was partly controlled by flagellar sigma factor FliA (σ28) in Pseudomonas putida KT244… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…BifA degrades c‐di‐GMP and lower intracellular c‐di‐GMP levels. Expression of the BifA is partly controlled by the flagellar sigma factor FliA in P. putida KT2440 . FliA deletion led to a twofold decrease in the transcriptional level of bifA .…”
Section: Discussionmentioning
confidence: 99%
“…BifA degrades c‐di‐GMP and lower intracellular c‐di‐GMP levels. Expression of the BifA is partly controlled by the flagellar sigma factor FliA in P. putida KT2440 . FliA deletion led to a twofold decrease in the transcriptional level of bifA .…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial secondary messenger cyclic diguanylate (c-di-GMP) regulates multiple important functions, including the transition from a planktonic lifestyle to a biofilm lifestyle and the biosynthesis of exopolysaccharides in the extracellular matrix of biofilms in many bacterial species (15). c-di-GMP is catalyzed by diguanylate cyclases (DGCs) and degraded by phosphodiesterases (PDEs).…”
Section: Introductionmentioning
confidence: 99%
“…A high intracellular c-di-GMP level drastically inhibits the biosynthesis of flagellin and bacterial motility but enhances the formation of biofilm. In contrast, a low c-di-GMP level strengthens bacterial motility and attenuates biofilm production in many bacteria (2, 5, 1114). In P.…”
Section: Introductionmentioning
confidence: 99%
“…This result could not be explained by the general model. Besides, our former study demonstrated that introducing multiple copies of PP_0914 ( bifA ) under the control of its own promoter into wild type KT2440 caused increased swimming motility and decreased biofilm formation (Xiao et al ., ). Here, in this study, we introduced multiple copies of PP_0914 under the control of a tac promoter into wild type KT2440 but found no obvious influence on biofilm formation (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, we wonder why the native and inducible promoters of PP_0914 lead to different phenotype. Our former study indicated that the expression of PP_0914 was controlled by both fliA and rpoD simultaneously (Xiao et al ., ), but detailed regulation of PP_0914 was still unclear. Future studies on the regulation of PP_0914 expression will help to answer this question.…”
Section: Resultsmentioning
confidence: 99%